Impact Attenuation of the Soft Pads and the Wearable Airbag for the Hip Protection in the Elderly - Jeong, Youngjae; Ahn, Soonjae; Kim, Jongman; Kim, Seongjung; Koo, Bummo; Ryu, Jeseong; Kim, Youngho (International journal of precision engineering and manufacturing, 2019)
Hip fractures caused by the falls in the elderly can lead to serious injuries that diminish their quality of life. The soft pads and wearable airbag have been developed and commercialized to prevent hip fractures of the elderly. In this study, the hip impact simulator was developed and the impact forces of six types soft pads and the hip protection airbag were measured by using the hip impact simulator. In addition, the distribution of the impact force and maximum contact area were also measured by attaching the pressure sensor on the surrogate pelvis of the hip impact simulator. Experiments were performed depending on the conditions protecting the surrogate pelvis (unpadded, soft pad, airbag) and the fall from 20 to 40 cm heights were repeated three times depending on each condition. The hip protection airbag decreased the mean pressure applied on the hip joint by decreasing a peak impact force according to the increased maximum contact area compared to the unpadded and soft pad conditions at all fall heights. Therefore, it can be concluded that the hip protection airbag can prevent the hip fracture by effectively attenuating impact force during falls in the elderly.